2020
DOI: 10.1186/s13104-019-4872-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced hepatotoxicity among TB/HIV co-infected patients in a referral hospital, Ethiopia

Abstract: ObjectivesAnti-tuberculosis drug-induced hepatotoxicity is a common serious adverse drug reaction. This study intended to determine the prevalence and associated factors of drug-induced hepatotoxicity among tuberculosis and human immunodeficiency virus co-infected patients in Dessie referral hospital northeast Ethiopia.ResultsIn this cross-sectional study 84 patients were enrolled retrospectively. Data from September 1/2015 to August 30/2018 were extracted from March 1/2019 to April 1/2019. Association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…The finding is comparable with results reported by Wondwossen A. et al (8%) in Ethiopia, 25 Rajani S et al (8%) from Nepal, 26 and Alsina N et al (8.8%) from Brazil. 27 However, this prevalence is lower than other studies in Ethiopia (20.2%), 28 and (11%), 11 as well in Brazil (36.7%), 29 and higher than that of the western world (4.3%). 31 The variation in the prevalence of anti-TB-DIH worldwide may be attributed to the differences in patients' characteristics, indiscriminate use of drugs, and the definition criteria of hepatotoxicity as different countries use their guidelines.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…The finding is comparable with results reported by Wondwossen A. et al (8%) in Ethiopia, 25 Rajani S et al (8%) from Nepal, 26 and Alsina N et al (8.8%) from Brazil. 27 However, this prevalence is lower than other studies in Ethiopia (20.2%), 28 and (11%), 11 as well in Brazil (36.7%), 29 and higher than that of the western world (4.3%). 31 The variation in the prevalence of anti-TB-DIH worldwide may be attributed to the differences in patients' characteristics, indiscriminate use of drugs, and the definition criteria of hepatotoxicity as different countries use their guidelines.…”
Section: Discussioncontrasting
confidence: 57%
“…27 In this study, patients whose BMI<18.5 kg/m2 were more likely to develop hepatotoxicity compared to patients who had BMI ≥18.5, a finding which is consistent with others. 17,28,30 The possible explanation of anti-TB drugsinduced hepatotoxicity in malnutrition may be due to depletion of glutathione stores, which makes patients more vulnerable to oxidative injuries, and the slower pace at which the liver metabolizes drugs. 26,31 In a previous study conducted in Ethiopian HIV positive and negative TB patients, the development of anti-TB drugs-induced hepatotoxicity had a significant association with a decrement in the immune status of the patients as measured by the CD4 count 32 Similarly, this study revealed a statistically significant association between low CD4 counts and the development of hepatotoxicity among the participants with decreased immune status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, 13 original articles consisting of 3676 study participants were included [31][32][33][34][35][36][37][38][39][40][41][42][43]. The research was carried out in Ethiopia's three (3) regions and one city administration.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%